Exploring supervision for volunteer community health workers in Mukono District, Uganda: An exploratory mixed-methods study. Issue 9 (2nd September 2022) - O'Donovan, James; Saul Namanda, Allan; Hamala, Rebecca
ABSTRACT: Community Health Worker (CHW) supervision is an under-researched area. This mixed-methods study engaged key stakeholders involved in CHW supervision in Mukono District, Uganda including CHWs ( n = 14), District Health Office officials ( n = 5), NGO programme managers ( n = 3) and facility-based health staff ( n = 3). Our study aimed to explore how supervision is currently conceptualised and delivered in this setting, the desired qualities of a potential supervisor, as well as the challenges regarding supervision and potential solutions to address these. To understand these concepts, we conducted structured surveys and individual interviews. Survey data were analysed in SPSS using descriptive statistics. Interview transcripts were thematically analysed in NVivo using conventional content analysis. This study revealed current CHW supervision in this context is fragmented. Supervision is perceived both as a means of motivating CHWs and facilitating ongoing training, as well as a way of holding CHWs accountable for their work. Stakeholders identified technical knowledge and expertise, strong interpersonal skills and cultural awareness as desirable qualities for a supervisor. Challenges surrounding supervision included a shortage of funding, a lack of guidelines on supervision, and infrequent supervision. To address these challenges, stakeholders proposed the need for increased funding, creating clearer job descriptions for supervisors, and in-person supervisory meetings.